STUDI PERENCANAAN TUBUH BENDUNGAN UTAMA (MAIN DAM) PADA PEMBANGUNAN WADUK BENDO KABUPATEN PONOROGO - Yeni Safitri; Eko Noerhayati; Bambang Suprapto (Universitas Islam Malang, 2020)
Some areas in Ponorogo Regency, East Java Province have a natural resource management problem, including flooding during the rainy season and lack of clean water when the dry season arrives. To overcome these problems, Bendo Dam is planned. The planning method begins by determining the location, hydrology, and hydraulic location, which finally obtained information to determine the design of the dam. From the results of the study we found the dimensions of the dam body based on Q1000th, including the dam height of 88 m, the elevation of the dam peak El.224.00, the length of the dam peak 15 m. The building material of the dam body has physical and mechanical properties that meet the existing criteria. discharge is 649.16 m3 / sec to get the magnitude of the river flow discharge using the Nakayasu HSS method. So that the total dam reservoir is 43,599 x 10 m3. Results Upstream slope stability after the dam has been built The normal state is 2.337> 1.5 (safe) and in an earthquake situation is 1.772> 1.1 (safe). The results of the analysis of the stability of seepage are as follows: 0.0094 m3 / sec < 0.05% < 21799.5 m3 / sec (safe). Keywords: Main Dam Planning, Urugan Type Dam, Bendo Dam.